Executing a business model change: Identifying key characteristics to succeed in volatile markets - Sebastian Allegretti; Sven Seidenstricker; Heiko Fischer; Sefkan Arslan (Leadership, Education, Personality. An Interdisciplinary Journal, 2021)
The world is changing, and with it comes the requirement that enterprises change to survive in today's volatile markets. However, the change does not just include launching a new product on the market but also changing the business model of the whole organisation. To sustain in today's fast-changing markets, companies have to detect new market opportunities on time, assess them and find a way to incorporate the most beneficial opportunities into their business. Without this awareness that a company must change with the changing market, it risks losing its significance in the market. Both the change of the business model and the change of the organisation are needed to succeed in the market. An outstanding example of such a company is Netflix. They have successfully changed their business model twice: first, from an online-DVD-rental service to a streaming provider and then, to a content provider. They were aware of upcoming new technologies on-time, evaluated them and planned the implementation in the market while the old technology was still profitable. The present work outlines the major changes in Netflix's business model and how they managed the change process successfully.
Keywords: 330; Adapt market opportunites; Alterable company; Business model; Business model canvas; Business model change; Successful change